A Percentile Based ADR for Mobile LoRaWAN Applications - Sarmento Neto, Geraldo A.; Silva, Thiago A. R.; Abreu, Pedro F. F.; Veloso, Arthur F. S.; M., Luis H. O.; R. Junior, José Valdemir (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2024: Anais do XLII Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2024)
The article presents a novel solution addressing the limitations of Adaptive Data Rate (ADR) mechanism in LoRaWAN networks, particularly in scenarios characterized by fluctuating channel conditions. By employing percentile-based statistical techniques, the proposed P-ADR optimizes Signal-to-Noise Ratio (SNR) estimation for adjusting transmission parameters, thereby enhancing reliability while preserving energy efficiency. Simulation results revealed superior performance of P-ADR, exhibiting an average Packet Delivery Ratio (PDR) advantage of approximately 5% over ADR+ and around 25% over standard ADR in mobile scenarios. The outcome highlights P-ADR potential as a viable and efficient alternative, improving reliability in LPWAN applications.